Fecal Microbiota Transplantation Via Nasogastric Tube for Recurrent Clostridium difficile Infection in Pediatric Patients. Issue 1 (January 2015) - Kronman, Matthew P.; Nielson, Heather J.; Adler, Amanda L.; Giefer, Matthew J.; Wahbeh, Ghassan; Singh, Namita; Zerr, Danielle M.; Suskind, David L.
Abstract : ABSTRACT: Fecal microbiota transplantation (FMT) is a safe and effective therapy for adults with recurrent Clostridium difficile colitis, but data regarding FMT in children are limited and focus on colonoscopic administration of FMT. We present 10 consecutive children who received FMT via nasogastric tube for treatment of recurrent C difficile infection. Median age was 5.4 years, and 30% were receiving simultaneous immunosuppression. Median follow-up was 44 days, and 90% of patients resolved their C difficile infection; one patient relapsed 2 months later after receiving antibiotics. FMT via nasogastric tube appears safe, well tolerated, and effective in treating pediatric recurrent C difficile colitis.